Non‐intrusive global/local analysis for the study of fine cracking. (18th January 2013) - Oliver‐Leblond, Cécile; Delaplace, Arnaud; Ragueneau, Frédéric; Richard, Benjamin
SUMMARY: The description of damaged zones in large scale structures can nowadays be assessed by means of a finite element approach using an appropriate damage model. Nevertheless, a fine description of cracking (crack pattern, crack length, crack opening, crack tortuosity) is of primary importance to satisfy new requirements in design codes, especially when dealing with structure durability. In this paper, a computational strategy to quantify cracking at structural case is proposed. A continuous damage model is used to perform a full resolution at the global scale. Then, a reanalysis (implemented as a post‐treatment) of the damaged zones is performed at the local scale with a discrete element model. A non‐intrusive and decoupled numerical scheme allows for a two‐scale analysis using each mechanical model (continuous as well as discrete) within its more efficient level. 2D and 3D test cases will be treated to illustrate the non‐intrusive global/local analysis. Copyright © 2013 John Wiley & Sons, Ltd.